Osmium nanozyme as peroxidase mimic with high performance and negligible interference of O2. Issue 47 (23rd November 2020) - He, Shaobin; Yang, Liu; Balasubramanian, Paramasivam; Li, Shujun; Peng, Huaping; Kuang, Ye; Deng, Haohua; Chen, Wei
Abstract : The Os nanozyme possesses a high peroxidase-like activity and negligible oxidase-like activity freeing the assays from the O2 and color interference. Abstract : Ongoing efforts have contributed to the exploration of peroxidase-like nanozymes while preserving their benefits in bioassays. Unfortunately, many peroxidase-like nanozymes still exhibit a low catalytic activity accompanied by oxidase-like activity with interferences of O2 and color which limit their applicability. Herein, we carried out a "green" approach to synthesize citrate-coated osmium nanozyme with a high peroxidase-like performance. Comprehensive experiments were validated in which the Os nanozyme could achieve excellent steady-state kinetic parameters and a high specific activity (393 000 Unit per g), which was better than those of most reported nanozymes. More significantly, the Os nanozyme possesses a higher peroxidase-like activity and negligible oxidase-like activity compared with those of common noble metal-based nanozymes (Pt and Au), freeing the corresponding assay system from the interference of O2 and color. In addition, the Os nanozyme presents robustness against complex environments and some metal ions that usually act as noble metal-based nanozymes. As a proof-of-concept, the Os nanozyme has been successfully employed to fabricate colorimetric assays for glucose and pyruvic acid detections with the associated color gradients. These findings collectively prove that the Os nanozyme could be a novel and promising peroxidase mimic candidate for bioassays and beyond.